The Potential of Sambas Malay Saprahan Tradition as a Culture-Based Biology Learning Resource - Andayani, Fitri; Setiadi, Anandita Eka; Rahayu, Hanum Mukti (Jurnal Pendidikan MIPA, 2024)
The process of modernisation makes a person forget his identity and identity as an Indonesian nation, so that it can result in the loss of noble cultural values and local traditions that risk resulting in the loss of cultural identity, one of which is saprahan which is a tradition of eating together in the Sambas Malay tribe. This study aims to identify plants and animals in the Malay saprahan tradition as a culture-based biology learning resource and analyse the potential of the saprahan tradition as a learning resource. The research method used is descriptive-explorative method, data collection through interviews, observation, identification, and response questionnaire. The results showed that there were 11 dishes in the saprahan tradition that used 20 types of plants and 5 types of animals. The results of the study are in accordance with the material classification of living things, food production, biodiversity. Diversity in the Sambas Malay saprahan tradition has the potential as a culture-based biology learning resource with an average score of 85% (Very Feasible).        Keywords: malay tribe sambas, learning resources, sarahan tradition.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1532-1548